2013
DOI: 10.2174/1871530311313010006
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Chronic Heart Failure: From Diabetic Cardiomyopathy to Therapeutic Approach

Abstract: Diabetes and chronic heart failure are interrelated conditions with major medical and economic impact that have to be treated as a distinct entity. Several pathological mechanisms have been investigated and proposed to explain the structural and functional changes associated with diabetic cardiomyopathy. These mechanisms are likely to act synergically and may potentiate one the other. This review outlines recent advances in the pathophysiological mechanisms implicated in the development and progression of diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 0 publications
0
21
0
2
Order By: Relevance
“…Previous studies (1,2,16) have demonstrated that myocardial fibrosis is a typical characteristic of diabetic cardiomyopathy. Both the deposition and disordered arrangement of type I and/or Ⅲ collagen and abnormal expression of MMPs/TIMPs, and cytokines TGF-b 1 or insulin-like growth factor 1 contribute to the development of myocardial fibrosis and cardiac diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies (1,2,16) have demonstrated that myocardial fibrosis is a typical characteristic of diabetic cardiomyopathy. Both the deposition and disordered arrangement of type I and/or Ⅲ collagen and abnormal expression of MMPs/TIMPs, and cytokines TGF-b 1 or insulin-like growth factor 1 contribute to the development of myocardial fibrosis and cardiac diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 98%
“…It reversed the altered blood glucose, HbA 1 and lipid levels, and plasma GLP-1 and insulin levels, and reduced fat deposition in diabetic myocardial and epicardial tissues, so sitagliptin may play an essential role in improving diabetic cardiac dysfunction and cardiomyopathy. Inflammation is a key pathophysiologic factor in diabetic cardiomyopathy (1,2,16,21), and is closely related to fat deposition. Ti et al (16) reported that TNF-a and IL-6 were overexpressed in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Heart failure is a common evolution of atherosclerosis, and several studies have shown the safety and the usefulness of anti-IL-1 treatment in this condition, a clinical setting in which anti-TNF treatment is contraindicated [78][79][80][81]. It is well known that the incidence of impaired cardiac function is increased strongly both in RA and T2D, leading to a poor prognosis [82,83]. In this context, our experimental data, showing a strong up-regulation of IL-1b MO derived from patients with both RA and T2D, may support the hypothesis that blocking IL-1b may be considered the best therapeutic strategy to treat these patients, due to the upregulation of this cytokine in these patients and to the safety shown during chronic heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Older age is a well-known risk factor for HF, an observation that our study extends to the CKD population. Diabetes mellitus is associated with a variety of myocardial metabolic, structural and functional abnormalities 32 , arterial stiffening 18;33 with increased pulsatile left ventricular afterload and coronary artery disease, all of which may contribute to its associated with HF in CKD. Similarly, the association between kidney function and incident HF has been reported in previous studies that included individuals with and without established CKD (e.g., older individuals) and has been shown to be independent of the presence of diabetes or hypertension at baseline 4;5;34;35 .…”
Section: Discussionmentioning
confidence: 99%